AgBr/BiOBr Nano-Heterostructure-Decorated Polyacrylonitrile Nanofibers: A Recyclable High-Performance Photocatalyst for Dye Degradation under Visible-Light Irradiation - Mingyi Zhang (Polymers, 2019)
Macrostructural flexible photocatalysts have been proven to have desirable recyclable properties during the photocatalytic degradation of organic pollutants in water. However, the photocatalytic activities of these photocatalysts are often unsatisfactory due to the fast recombination of charge carriers and the limited surface active sites. Herein, we developed a novel flexible photocatalyst of AgBr/BiOBr/polyacrylonitrile (PAN) composite mats (CMs) through the controllable assembly of AgBr/BiOBr nano-heterostructures on electrospun polyacrylonitrile nanofibers (PAN NFs) via a three-step synthesis route. The component ratio of AgBr to BiOBr in the CMs could be easily adjusted by controlling the in situ ion exchange process. The charge−transfer process occurring at the interface of the AgBr/BiOBr nano-heterostructures strongly hindered the recombination of photoinduced electron−hole pairs, thereby effectively enhancing the photocatalytic activity of the AgBr/BiOBr/PAN CMs. Meanwhile, the unique hierarchical inorganic/organic heterostructure of the AgBr/BiOBr/PAN CMs not only led to good flexibility, but also provided an abundance of active sites for photocatalytic reactions. Upon visible-light irradiation, AgBr/BiOBr/PAN CMs with an optimal ratio of AgBr to BiOBr components exhibited both enhanced photocatalytic activity and excellent separability during the degradation of methyl orange in water compared to the BiOBr/PAN CMs.